KAPASITAS LENTUR PLAT BETON BERTULANG BAMBU PETUNG POLOS - Hana Hantara; Agus Setiya Budi; Achmad Basuki (Program Studi Teknik Sipil FT UNS, 2014)
Forest is one of the biggest timber for a country, especially Indonesia. Forest products in Indonesia taken in excess without thinking about theregeneration of new plants. To that end, in Indonesia is carried out afforestation or reforestation of denuded forest in order to get back to normal.Other construction materials as an alternative to steel such as wood and bamboo are being carried out. Along with the rapid growth of thepopulation growth rate of development in Indonesia. As a result of this increase in development, needs reinforcing steel prices rose to becomeexpensive. That is why it is necessary looking for a new alternative replacement of steel reinforcement in concrete, namely bamboo. Bamboo can berefurbished and have a high tensile strength tensile steels approached. Bamboo is used instead of concrete reinforcing steel plate include bambooPetung plain. This bamboo reinforced concrete plate observed include flexural capacity, deflection, compressive strength and location of the positionof the concrete slab collapse when loaded. The method used in this study is an experimental method to the test specimen in the form of a singlereinforced concrete slab measuring 600 mm x 400 mm x 100 mm steel and bamboo petung bertulangan plain with a load that is placed amidlandscape and evenly distributed as the weight of two points on the test object with length L/3. Concrete slab placement system used in this study isone-way with the placement of joints. Flexural capacity of concrete slab testing done at the time the specimen was 28 days. The results of theanalysis of steel reinforced concrete plate can withstand a maximum load of 6450 kg with a deflection of 5.99 mm while the test results ofreinforced concrete plate specimen petung plain bamboo can withstand a maximum load of 2200 kg or 34.11% compared with the deflection ofsteel plate reinforced by 2.47 mm. Flexural capacity of reinforced concrete slab analysis results produce steel 0.3976 ton-m value and the testresults obtained by the average value of 0.5236 ton-m while the flexural capacity of reinforced concrete slab analysis results petung plain bambooproduces 0.2853 ton-m value and the test results obtained by the average value of 0.1730 ton-m. These results indicate that the test results ofreinforced bamboo plate bending capacity 33.04% of the test results of reinforced steel plate.